Viskningar och rop [videorecording (DVD)] = Cries and whispers - Bergman, Ingmar, 1918-2007; Ullmann, Liv; Andersson, Harriet; Thulin, Ingrid; Josephson, Erland, 1923-2012 (Criterion collection, 2001)
A story of four women's search for spiritual peace. Agnes is dying of cancer and is visited one last time by her two sisters, Karin and Maria. These two become entangled in feelings of jealousy, manipulation and selfishness. Yet Agnes is able to transcend her sisters' pettiness to remember moments of staggering beauty as well as horror.